Crossing religious boundaries: Islam, Christianity and 'Yoruba religion' in Lagos, Nigeria - Janson, Marloes (The International African library, 2021)
"Welcome to Lagos; here everything is possible' were the words with which my research collaborator Dr Mustapha Bello greeted me when I first arrived in Nigeria's former capital in 2010. That 'everything is possible' in this megacity, I soon discovered when we drove by a three-storey building that, as Mustapha pointed out to me, hosted a mainline church, a Pentecostal church, and a mosque. Although he described himself as a 'die-hard Muslim', Mustapha did not seem to have any problem with a mosque sharing the same space with a church. Underlining the pragmatism that characterizes Lagosians, he argued that this was an 'economic use of space'. While in this particular building different religious institutions occupied different floors, I also came across movements mixing Islam and Christianity, sometimes in interaction with 'Yoruba religion',1 during the course of my nine-month ethnographic field research in Lagos"--